1992
DOI: 10.1530/jrf.0.0950513
|View full text |Cite
|
Sign up to set email alerts
|

Histology of ovaries of female rabbits immunized with deglycosylated zona pellucida macromolecules of pigs

Abstract: Female rabbits (n = 36, 6 per group) were immunized with: (i) solubilized isolated porcine zona pellucida (SIZP), which contains ZP1, 82 kDa; ZP3 alpha, 55 kDa; and ZP3 beta, 55 kDa; (ii) a purified preparation of ZP3 alpha and ZP3 beta (ZP3); (iii) purified endo-beta-galactosidase digested glycoproteins ZP3 alpha-(EBGD) and (iv) ZP3 beta-(EBGD) (each about 30% deglycosylated); (v) chemically deglycosylated core proteins ZP3 alpha-(DG) and (vi) ZP3 beta-DG (each greater than 92% deglycosylated). Rabbits inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…One of the animals (Fig. 2) (Jones et al, 1992). In primate models, the use of deglycosylated ZP3 in baboons (Dunbar el al, 1989) showed decreased concentrations of oestrogen followed by a cessation of ovulation, whereas deglycosylated ZP3ß in mar¬ moset monkeys (Paterson et al, 1992) (Millar et al, 1989), whereas the same peptide in complete Freund's adjuvant (CFA) given to (C5 7B1/6 A/J) Fj mice causes severe autoimmune oophorites (Rhim el al, 1992 (Mahi-Brown et al, 1985) showed that the antibody response generated by using alum was low, but sufficient to protect the animal from pregnancy in the first cycle after immunization.…”
Section: Methodsmentioning
confidence: 99%
“…One of the animals (Fig. 2) (Jones et al, 1992). In primate models, the use of deglycosylated ZP3 in baboons (Dunbar el al, 1989) showed decreased concentrations of oestrogen followed by a cessation of ovulation, whereas deglycosylated ZP3ß in mar¬ moset monkeys (Paterson et al, 1992) (Millar et al, 1989), whereas the same peptide in complete Freund's adjuvant (CFA) given to (C5 7B1/6 A/J) Fj mice causes severe autoimmune oophorites (Rhim el al, 1992 (Mahi-Brown et al, 1985) showed that the antibody response generated by using alum was low, but sufficient to protect the animal from pregnancy in the first cycle after immunization.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using purified deglycosylated native or recombinant ZP proteins have identified specific ZP immunogens which elicit antibodies that inhibit fertility and sperm binding to ZP without altering ovarian follicular development [Millar et al, 1989;Aitken et al, 1990;Sacco et al, 1991;Jones et al, 1992;VandeVoort et al, 1995]. These are in contrast to studies in which antibodies to different ZP antigens alter ovarian follicular development or cause autoimmune oophoritis Jones et al, 1992;Rhim et al, 1992;VandeVoort et al, 1995;Aitken et al, 1996].…”
Section: Effect Of Antibodies Against Zp Proteins On Ovarian Folliculmentioning
confidence: 99%
“…ZP protein was prepared as described previously ( Jones et al 1992) using pig ovaries from a local abattoir (Perth, WA, Australia). Briefly, ovaries were passaged through a descending series of molecular sieves and zonae solubilized and concentrated (!100) using an ultrafiltration cell.…”
Section: Porcine Zp Vaccinementioning
confidence: 99%
“…The extraction procedure was modified from Jones et al (1992). Briefly, ovaries were homogenized and passed through a series of molecular sieves, centrifuged at 1800 g for 12 min at 4 8C and subjected to three rounds of freezing and thawing.…”
Section: Preparation Of Native Feline Zpmentioning
confidence: 99%
See 1 more Smart Citation